2014
DOI: 10.1016/j.psychres.2014.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and lung function in schizophrenia: A pilot study

Abstract: This pilot study aimed to explore relationships between metabolic and lung functions in patients with schizophrenia. Eighty patients with schizophrenia (55♂; 36.8±10.0 years) underwent a spirometry, were screened for metabolic syndrome (MetS), performed a 6-minute walk test (6MWT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…18 Further, it is assumed that the association between metabolic syndrome and restrictive lung disease is mediated by abdominal obesity. 14,36 However, other mechanisms, such as insulin resistance and inflammation, have also been suggested. 14,36 Diabetes has been independently associated with impaired lung function and restrictive lung disease in particular.…”
Section: Spirometry Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Further, it is assumed that the association between metabolic syndrome and restrictive lung disease is mediated by abdominal obesity. 14,36 However, other mechanisms, such as insulin resistance and inflammation, have also been suggested. 14,36 Diabetes has been independently associated with impaired lung function and restrictive lung disease in particular.…”
Section: Spirometry Resultsmentioning
confidence: 99%
“…To our knowledge, there are only three previous studies that have measured lung function with spirometry in people with psychotic disorders. 1214 The two most recent studies by Vancampfort et al were based on the same sample of 80 predominantly male patients with schizophrenia: the first study found an association between impaired walking ability and reduced lung function; and the second study an association between metabolic syndrome and restrictive lung disease in patients with schizophrenia. 13,14 In the first study the authors also reported reduced spirometry values in patients with schizophrenia compared with healthy controls, but whether restrictive lung disease is more common in schizophrenia compared with the general population was not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…It might be postulated that these inflammatory processes may cause pathological microvascular changes that can affect gas transfer across the alveolar-capillary membrane, which in turn may affect the circulatory, respiratory, and muscular systems involved in supplying oxygen to the body (Ostermann et al, 2012). A previous pilot study in patients with schizophrenia already demonstrated that the presence of MetS is associated with an increased prevalence of restrictive lung dysfunction (Vancampfort et al, 2014b), which on its turn might impair the ability to perform physical activities (Vancampfort et al, 2014a). In an additional analysis we did find that the shuttle run test performance in people with MetS was significantly worse than in those without MetS (31.2±7.4 versus 25.6±6.5, P=0.027).…”
Section: General Findingsmentioning
confidence: 99%
“…The underlying mechanisms for this increased cardiometabolic risk are multifactorial and include adverse effects of pharmacological treatments (De Hert et al, 2009;Mitchell et al, 2013aMitchell et al, , 2013b; poorer access to and quality of physical healthcare (Mitchell et al, 2009); and an unhealthy, sedentary lifestyle exacerbated by psychiatric symptoms (Vancampfort et al, 2014b(Vancampfort et al, , 2014c. In the general population, in addition, low aerobic fitness has been recognized as an established behavioral risk factor for CVD and premature mortality (Gill and Malkova, 1998;Wei et al, 1999).…”
mentioning
confidence: 99%